Tinjauan Ekonomi Syariah Tentang Pemberlakuan Tarif Ekspor Amerika Serikat - Majid, Abdul; Mawardi, Imam (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2025)
The imposition of export tariffs by the United States on several of its trading partners has triggered significant global economic impacts. From the perspective of Islamic economics, such policies require in-depth analysis, as they may lead to injustice in international trade—contrary to the core principles of justice (al-‘adalah), balance (tawazun), and mutual benefit (maslahah) upheld in the Islamic economic system. This study aims to examine U.S. export tariff policies through a qualitative-descriptive approach based on Islamic economic principles. The findings indicate that excessive protectionism, such as high export tariffs, can distort markets, harm developing countries, and exacerbate global economic inequality. Within the framework of maqashid al-shariah, these policies may hinder the realization of public welfare (maslahah ‘ammah). Therefore, a more equitable and balanced approach to international trade is necessary—one that emphasizes ethical and moral principles rooted in Islam. This study recommends more inclusive international dialogue and the implementation of global trade policies aligned with the values of social and economic justice in Islam.